Proceedings of the 2019 4th International Conference on Humanities Science and Society Development (ICHSSD 2019) 2019
DOI: 10.2991/ichssd-19.2019.66
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Effect of Tourism Impact Perception on the Subjective Well-being of Community Residents

Abstract: Rapid social development has raised people's income level, and tourism has increasingly become a part of our lives. Dujiangyan City, Sichuan Province is a famous tourist destination, the development of tourism is closely related to the local community residents. This paper explores its impact on residents' subjective well-being from the perspective of tourism impact perception. The results show that tourism revenue perception has a significant positive impact on the subjective well-being of community residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…None of the other variables reached scores indicating the existence of a significant impact or influence on the pilgrims' satisfaction and, consequently, the differences of perception determined by those aspects were not analyzed. These results were in line with other studies [56] that demonstrated the existence of differences of perception determined by certain features of the respondents' socio-demographic profile: age, education, and income level [65]. However, in the present study, the rather weak connection between satisfaction and certain socio-demographic factors may be explained by the high level of faith, characteristic of both pilgrims attending the Iasi event and Romanians in general, which causes them to consider the ritual itself the main purpose of the journey, and this happens irrespective of gender, education and income levels, or professional status.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…None of the other variables reached scores indicating the existence of a significant impact or influence on the pilgrims' satisfaction and, consequently, the differences of perception determined by those aspects were not analyzed. These results were in line with other studies [56] that demonstrated the existence of differences of perception determined by certain features of the respondents' socio-demographic profile: age, education, and income level [65]. However, in the present study, the rather weak connection between satisfaction and certain socio-demographic factors may be explained by the high level of faith, characteristic of both pilgrims attending the Iasi event and Romanians in general, which causes them to consider the ritual itself the main purpose of the journey, and this happens irrespective of gender, education and income levels, or professional status.…”
Section: Resultssupporting
confidence: 93%
“…Age was also important for evaluating the pilgrims' satisfaction level; for example, young people generally registered the lowest scores. Although we did not identify a great number of studies focused on evaluating this aspect, the authors who have approached the topic suggest that pilgrims perceive the level of satisfaction with certain religious events or journeys they participate in differently, depending on a series of demographic characteristics, such as the psychological profile [26], age, gender, education and income levels [56,65]. The results confirm the additional hypothesis Ha2: "Pilgrims' level of satisfaction with the event organized by the Iasi Metropolitan Cathedral differs significantly depending on respondents' age" and Hypothesis Ha4: "Pilgrims' level of satisfaction with the event organized by the Iasi Metropolitan Cathedral differs significantly depending on their faith (in God).…”
Section: Discussion Limits and Further Researchmentioning
confidence: 99%
“…In combination of general situations of eco-tourism development, as well as the uniquely natural, social, economic characteristics in Kanas tourist destination, the daily carrying capacity of spatial resource, ecological environment and economic environment in 2018 are obtained by applying related formulas and barrel theory. In the analysis of local history and reality, the daily carrying capacities of people’s psychological and socio-cultural environment are emerged 64 . Therefore, based on the calculation and analysis, the vectors S 1 / S 2 / S 3 corresponding to the saturated / optimal / deficient standard patterns are determined.…”
Section: An Exemplary Case Study On the Eco-tourism Environmental Car...mentioning
confidence: 99%
“…The maximum daily wastewater effluent of Kanas tourist destination is 590.50 m 3 / day. Sewage treatment capacity reaches 413.35 m 3 / day, given the sewage treatment rate as high as 70%, due to the continuous improvement of the drainage facilities 64 . The following can be deduced from this, …”
Section: An Exemplary Case Study On the Eco-tourism Environmental Car...mentioning
confidence: 99%
See 1 more Smart Citation